Advanced Structural Ceramics - Basu, Bikramjit; Balani, Kantesh (Hoboken, New Jersey : Wiley, 2011)
This book covers the area of advanced ceramic composites broadly, providing important introductory chapters to fundamentals, processing, and applications of advanced ceramic composites. Within each section, specific topics covered highlight the state of the art research within one of the above sections. The organization of the book is designed to provide easy understanding by students as well as professionals interested in advanced ceramic composites. The various sections discuss fundamentals of nature and characteristics of ceramics, processing of ceramics, processing and properties of toughened ceramics, high temperature ceramics, nanoceramics and nanoceramic composites, and bioceramics and biocomposites.
Frontmatter -- Color Plates -- Section One: Fundamentals of Nature and Characteristics of Ceramics. Ceramics: Definition and Characteristics -- Bonding, Structure, and Physical Properties -- Mechanical behavior of Ceramics -- Section Two: Processing of Ceramics. Synthesis of High-Purity Ceramic Powders -- Sintering of Ceramics -- Thermomechanical Sintering Methods -- Section Three: Surface Coatings. Environment and Engineering of Ceramic Materials -- Thermal Spraying of Ceramics -- Coatings and Protection of Structural Ceramics -- Section Four: Processing and Properties of Toughened Ceramics. Toughness Optimization in Zirconia-Based Ceramics -- S-Phase SiAlON Ceramics: Microstructure and Properties -- Toughness and Tribological Properties of MAX Phases -- Section Five: High-Temperature Ceramics. Overview: High-Temperature Ceramics -- Processing and Properties of TiB and ZrB with Sinter-Additives -- High-Temperature Mechanical and Oxidation Properties -- Section Six: Nanoceramic Composites. Overview: Relevance, Characteristics, and Applications of Nanostructured Ceramics -- Oxide Nanoceramic Composites -- Microstructure Development and Properties of Non-Oxide Ceramic Nanocomposites -- Section Seven: Bioceramics and Biocomposites. Overview: Introduction to Biomaterials -- Calcium Phosphate-Based Bioceramic Composites -- Tribological Properties of Ceramic Biocomposites -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Ceramic materials; Ceramic-matrix composites; TECHNOLOGY & ENGINEERING -- Material Science; Ceramic materials; Ceramic-matrix composites; Electronic books; Electronic books